Effects of diets with varying protein levels on rumen ciliate protozoa in buffaloes (Bubalus bubalis L.) - Franzolin Neto, Raul; Nogueira Filho, José Carlos Machado; Oliveira, Maria Ely Miserochi de (Pesquisa Agropecuaria Brasileira, 1991)
Four rumen canulated buffaloes in a latin square design were used to investigate the effect of protein levels upon the concentration of ciliate protozoa in the rumen. The buffaloes were fed twice daily with four rations of increasing crude protein levels: 8.7%, 10.5%, 12.3% and 14.3% CP. The rations were composed of 70% roughage (Panicum maximum Jcq. var. gongyloides grass) and 30% concentrate (corn grain and toasted soybean grain). Eight genus of ciliate protozoa were identified and counted. A significant increase in the total protozoal numbers, Entodiniun spp., Diplodinium spp. and Elytroplastron bubali was observed in the 12.3% CP ration. The mean of total protozoal concentration was 8.48 x 104 ml of rumen liquid and the percentage of Entodinium spp. was 67.2% following by Diplodinium spp. at 16.0%.